Heterogeneous fenton-like reaction using Fe3-xMnxO4-MKSF composite catalyst for degradation of acid orange II dye. (November 2019) - Alrozi, R; Zubir, N A; Amir, N; Abdul Rahman, N N A; Kamaruddin, M A
Abstract: The selection of a good catalyst support is crucial in contributing towards the enhancement catalytic activity of a catalyst. Therefore, in this study, the influence of montmorillonite KSF (MKSF) clay loading in relation with catalytic performance of the resultant composite catalyst has been investigated. The MKSF clay loading were varied at x = 20, 40, 60 and 80 wt%, respectively. Interestingly, Fe3-0.3 Mn0.3 O4 -MKSF(40wt%) has shown greater catalytic performance up to 98% of acid orange II (AOII) dye removal in comparison to the Fe3-0.3 Mn0.3 O4 and Fe3 O4 catalysts. The AOII degradation kinetic using Fe3-0.3 Mn0.3 O4 -MKSF(40wt%) was fitted well with first-order reaction kinetic and the reaction rate increased in the order of Fe3 O4 >Fe3-0.3 Mn0.3 O4 >Fe3-0.3 Mn0.3 O4 -MKSF(40wt%). It also demonstrated in the work that Fe3-0.3 Mn0.3 O4 -MKSF(40wt%) catalyst can be reused several times without affecting its efficiency. Thus, it can be suggested that MKSF clay as catalyst support played a significant role in enhancing the overall catalytic performance of Fe3-0.3 Mn0.3 O4 catalyst during the heterogeneous Fenton-line reaction as well as the degradation kinetics of the AOII solutions.